Epidemiological Information on Anatomical Variations of the Sternum: Sternal Foramen and Variant Xiphoid Morphology in Dried Adult Human Sternum in Ethiopia - Alemayehu Shiferaw Lema; Amanuel Oljira Raga (Achievements and Challenges of Medicine and Medical Science Vol. 6, 2024)
Background: The human sternum comprises three components such as the manubrium, the mesosternum (body), and the xiphoid process. The sternum exhibits unique anatomical variations with major clinical and forensic implications. Purpose: This study is devoted to providing baseline epidemiological information about the sternal foramen and variant xiphoid morphology in Ethiopia. Two extremely interesting and unusual variations of the sternal foramen are also discussed. Methods: This observational study was carried out using dried adult human sternum obtained from skeletal remains samples brought for medicolegal examination over a period of 4 years. A total of 94 dried adult human sternums (66 males (70.2%) and 28 females (29.8%)) were obtained with an age range of 21 to 57 years and a mean age at death of 38.383 ± 11.3480 years. Data were analyzed using SPSS version 26.0. Continuous data were described in terms of the mean and compared using the Mann–Whitney U test. Dried human sternum specimens were morphologically examined, and morphometric parameters were recorded and photographed. Results: A sternal foramen was found in 18 specimens (19.1%); 17 were male and one was female. A single sternal foramen was observed in 83.3% (n=15/18) of the sternal bodies and 11.1% (n=2/18) of the xiphoid processes (both males). In addition, a double sternal foramen was observed in a single male specimen on the mesosternum and xiphoid process. The most common sternal foramen site was at the fifth costochondral junction level. The xiphoid process was present in 77 samples and ended as a single process in 83.1% (n=64/77) of samples. In 15.6% (n=12/77) of the samples, the xiphoid process was bifurcated and trifurcated in a single male (1.3%) specimen. The incidence of Sternal foramen varies in different studies from different populations and reported incidence data on Sternal foramen from different populations ranging from 3.1 to 18.3%. Conclusions: The sternal foramen and variation in xiphoid morphology are common anatomical variations in Ethiopia. The findings of the current study highlight the necessity of strict precautionary measures during sternal procedures in this study population. Clinicians, radiologists, and anthropologists need to be aware of these variations, and their presence should be taken into consideration in everyday practice. In addition, such incidental findings during radiologic and autopsy procedures should be properly evaluated to avoid misdiagnosis and misinterpretation of such findings as traumatic or pathologic conditions.